Strategies and tactics of the Moro Islamic Liberation Front (MILF) in the Southern Philippines - Shamsuddin L. Taya (Universiti Utara Malaysia Press, 2009)
This book reveals the strategies and tactics of the Moro Islamic Liberation Front (MILF) in the Southern Phillipines. It looks at the political, military and economic strategies and tactics of the MILF in its quest to liberate the Bangsamoro homeland and its people from the clutches of the Government of the Republic of the Phillipines (GRP) and its agents.